2020
DOI: 10.1123/apaq.2019-0104
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Developmental Trajectories of Elite Able-Bodied and Wheelchair Basketball Players

Abstract: Little is known about the factors influencing Paralympic athletes’ journey to expertise and whether these athletes have trajectories similar to those of their able-bodied (AB) peers. The purpose of this project was to compare the developmental trajectories of wheelchair and AB basketball players. A total of 150 participants completed the Developmental History of Athletes Questionnaire. Results revealed that while AB athletes reached early career milestones at a significantly younger age, athletes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…These age-related performance trajectories continue to be frequently investigated across sports for able-bodied athletes, 5–9,12 but equivalent research for para athletes has only recently started to emerge 13–15 . While several generic athlete development models offer support and guidance to coaches, 16–18 these were developed based able-bodied athletes, and it has been cautioned that they may reflect performance trajectories of para athletes poorly 14 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These age-related performance trajectories continue to be frequently investigated across sports for able-bodied athletes, 5–9,12 but equivalent research for para athletes has only recently started to emerge 13–15 . While several generic athlete development models offer support and guidance to coaches, 16–18 these were developed based able-bodied athletes, and it has been cautioned that they may reflect performance trajectories of para athletes poorly 14 .…”
mentioning
confidence: 99%
“…While several generic athlete development models offer support and guidance to coaches, 16–18 these were developed based able-bodied athletes, and it has been cautioned that they may reflect performance trajectories of para athletes poorly 14 . The para-specific reports on age and performance have shown that wheelchair basketball players, 14 para track-and-field athletes, 15 and para swimmers, 13 peak later than what is typically reported for able-bodied equivalents. Previous research has reported that para athletes often start to participate in sports at an older age, which may partially explain these discrepancies 14 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Arguably, there are similarities between the two sporting Games (i.e., Quadrennial format and peak event for most competing athletes and their coaches, intense environments, increased media exposure, and prestigious accolades [21][22][23]; however, it is important to consider that there may be challenges that are unique to Paralympic sport contexts. For example, there are similarities between able-bodied and Para sport coaching (i.e., the value of using autonomy-supportive strategies), but there are also aspects when coaching elite athletes with disabilities that require a more adaptive approach (i.e., tailoring training to athletes' unique abilities or dealing with social stigmas in public settings; [20,[24][25][26][27][28][29][30]. In addition, there is considerable literature noting how Paralympic coaches need to adapt and utilize different methods of learning (i.e., formal, nonformal, informal) to combat the lack of resources and support available to them [31][32][33][34].…”
Section: The Paralympic Contextmentioning
confidence: 99%